THE SIGNIFICANCE AND ROLE OF PROVIDING THE RIGHT TO FREEDOM AND PERSONAL VIOLENCE IN NATIONAL AND INTERNATIONAL LAW (Intent Research Scientific Journal, 2023)
This article describes the international and national mechanisms for the protection of human rights, the historical basis of their establishment, legal status, and practical significance.